Development E-Learning to Improve Student Activity with Technological Pedagogical and Content Knowledge - Setuju, S; Rahmat Setiadi, Bayu; Ratnawati, Dianna; Widowati, Asri; Wijayanti, Astuti; Bintoro Johan, Arif; Robiasih, Hasti; Nurdiyanto, Heri (International Journal of Engineering and Technology, 2018)
Industrial era 4 is the era with digitalization in various fields, including education. The need for e-learning based learning is essential to develop. The development of learning with TPACK framework (Technological Pedagogical and Content Knowledge) through learning e-learning in this research is designed by using Edmodo application. The purpose of the learning development is to internalize the technology into pedagogic, teaching materials and knowledge packed with online learning. The development model uses the Research and Development design of the 4-D model. Stage 4-D includes: define, design, develop and disseminate. The results showed that the model of online learning for the learning media course could increase the learning activity and the students can learn independently with the existing technology.Â Â